Assessing the Craft: Use of Specific Descriptors as Guide for Evaluating Instructional Materials - Dorado, Felicity Anne Aretha (English Journal Antartika, 2024)
Instructional materials created by teachers blend creativity with academic expertise. Like professional writers, teachers must communicate ideas, adapt content for their students, and keep them engaged through lesson plans, activities, and assessments. These materials are regularly updated based on student feedback, similar to how writers revise their drafts. Teachers use specialized knowledge and experience to design adequate resources that meet different learning needs. With the new K-12 Curriculum in the Philippines, teachers are increasingly seen as both instructors and creators of knowledge. This paper reviews DepEd materials and evaluation rubrics to assess how well these instructional materials work from a teacher’s perspective. Teachers can greatly improve instructional materials, boost student thinking, and enhance learning by taking on a critical role. While reviewing materials takes time, technology like AI plagiarism checkers can help speed up the process. Researchers agree that regularly updating methods and assessments is important because knowledge and insights change over time, and feedback may highlight areas for improvement. Changes in technology and society also require updates to keep materials relevant and effective. Therefore, careful evaluation is needed to choose suitable materials. Schools should support materials made by experienced educators, not just good writers. Academic boards should invest in quality assurance with dedicated revision, auditing, and editing teams to ensure ongoing quality.